Pengembangan Keterampilan Berpikir Historis melalui Pembelajaran Sejarah - Miskawi, Khoirul Anwar, Maulana Yusuf Arrasuly, Hieronymus Purwanta (LP4MK STKIP PGRI Lubuklinggau, 2025)
Abstract Learning history and developing historical thinking skills is an important component of a curriculum that aims to improve students' understanding of historical events and contexts. Analytical literature study methods used for sources, understanding context, and applying various perspectives are some of the ways to improve historical thinking skills in this article. The results of this study show that learning history and developing historical thinking skills is an important aspect of education. These skills help students understand past events, analyze data critically, and bring history to bear on contemporary issues. Through an approach that emphasizes context, evidence, and perspective, students can develop critical thinking skills, awareness of cultural identity, and empathy. Overall, historical thinking skills enhance students' understanding of history and prepare them to become active and responsible citizens. Therefore, it is important for educators to integrate this approach into the curriculum. Keywords: Development, Historical Thinking, Learning, History.